2021
DOI: 10.7150/ijbs.57164
|View full text |Cite|
|
Sign up to set email alerts
|

Ferroptosis-related Genes for Overall Survival Prediction in Patients with Colorectal Cancer can be Inhibited by Gallic acid

Abstract: Colorectal cancer (CRC) is one of the most deadly malignant tumors, which seriously threatens human health. Ferroptosis, a new type of iron-dependent cell regulatory necrosis. Inducing ferroptosis of tumor cells is regarded as a potential treatment strategy. However, the prognostic value of ferroptosis-related genes in CRC remains to be further elucidated. Gallic acid, widely used in the chemical, pharmaceutical, and food fields, is a dietary supplement with potential prescription significance. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Zhang et al found that active ingredients of Rheum palmatum L. had anti-lung cancer effect via induction of apoptosis by applying network pharmacology method 18 . Hong et al used bio-information analysis method to found gallic acid can inhibit the growth of colon cancer cells, and its mechanism of action is related to ferroptosis 19 . In this study, we used a combination of bio-information analysis and network pharmacology, as well as molecular docking, to simulate the possible mechanisms of TSA treatment for LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that active ingredients of Rheum palmatum L. had anti-lung cancer effect via induction of apoptosis by applying network pharmacology method 18 . Hong et al used bio-information analysis method to found gallic acid can inhibit the growth of colon cancer cells, and its mechanism of action is related to ferroptosis 19 . In this study, we used a combination of bio-information analysis and network pharmacology, as well as molecular docking, to simulate the possible mechanisms of TSA treatment for LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, honokiol, a biphenolic compound originally extracted from Magnolia grandiflora that has been reported to exert anticancer effects through the inhibition of GPX4 and activation of ferroptosis in CRC cells [137]. Besides, gallic acid, Chinese matrine, and Chinese herb Curcumae rhizoma have also been shown to induce ferroptosis in CRC cells by inhibiting GPX4 and SCL7A11 [138][139][140]. However, the underlying mechanism by which these bioactive components regulate the expression of GPX4 and SLC7A11 is still largely unknown and require further study.…”
Section: Effects Of Dietary Nutrients and Phytochemicals On Ferroptosis And Gastric Diseasesmentioning
confidence: 99%
“…In Bai's research [23], ziyuglycoside II induced apoptosis through the accumulation of reactive oxygen species (ROS), triggered complete autophagic flux, and improved the sensitivity of 5-fluorouracil in colorectal cancer cells. Gallic acid, a major compound of phenols in Sanguisorba officinalis L., could bind to ferroptosis-related targets and regulate the expression of corresponding proteins; ferroptosis inhibitors reversed the experimental results, improving CRC by regulating ferroptosis [24]. Another compound named 3,3 ,4trimethylellagic acid (TMEA), a tannin compound isolated from Sanguisorba officinalis L., executed its anti-cancer activity by inducing apoptosis and inhibiting angiogenesis in CRC cells via the apoptotic and VEGF/PI3K/AKT/mTOR pathways [25].…”
Section: Discussionmentioning
confidence: 99%